Feeding & nutritional requirements of young fish - Kamarudin, Mohd Salleh (Universiti Putra Malaysia Press, 2015)
The world annual total fisheries catch continues to decline, a trend observed since 1996. If timely remedial actions are not taken, scientists believe that the ocean seafood stocks and supply will soon be depleted. Aquaculture seems to be the only realistic solution to reduce the pressure on capture fisheries and to supply most of the seafood in the future. Currently, almost half of the world's total fisheries production is contributed by the aquaculture industry,On average, a Malaysian consumes almost 60 kg of seafood per year. Malaysia is tied with Korea for T" place among the top world seafood consumers. Although Malaysia has achieved ≥100% self sufficiency level (SSL) in seafood supply, more than 80% of its seafood comes from capture fisheries. Meanwhile, Malaysia's aquaculture industry has been experiencing an average annual growth rate of23.4% over the last ten years, although most of the growth has been contributed by seaweed production rather than food fish. Thus, in terms of ensuring its food security, Malaysia must increase its cultured food fish production to meet at least 50% of its seafood SSL. The main bottleneck in the expansion and growth of food fish aquaculture in Malaysia is the insufficient seed or fry supply. Despite breakthroughs in the induced breeding of many fish species, use of the right feed remains a major obstacle during the larviculture stage as larval feeding behavior, mouth gape, digestive capacity and nutrient requirements vary with species, growth stage or age. For successful larval and postlarval rearing, each fish species must be given a specific diet comprising the right particle size and nutrients at the correct feeding ration and frequency at each growth stage.